2012
DOI: 10.1523/jneurosci.2176-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Aging Affects Neural Precision of Speech Encoding

Abstract: Older adults frequently report they can hear what is said but cannot understand the meaning, especially in noise. This difficulty may arise from the inability to process rapidly changing elements of speech. Aging is accompanied by a general slowing of neural processing and decreased neural inhibition, both of which likely interfere with temporal processing in auditory and other sensory domains. Age-related reductions in inhibitory neurotransmitter levels and delayed neural recovery can contribute to decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
345
6
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(397 citation statements)
references
References 86 publications
44
345
6
2
Order By: Relevance
“…However, these compensatory mechanisms come at the cost of reduced synchrony of neural representations (Rabang et al 2012). This could result in the some of the decreased EFR amplitudes with age observed in this study and elsewhere (Clinard et al 2010;Parthasarathy and Bartlett 2011;Anderson et al 2012). However, modeling the loss of AN fibers and synapses recreated the majority of the trends observed due to age in this study, suggesting peripheral contributions for the decrease in EFR amplitudes at high SNRs and large AM depths.…”
Section: Effects Of Aging In Processing Simultaneous Sam Tonessupporting
confidence: 49%
“…However, these compensatory mechanisms come at the cost of reduced synchrony of neural representations (Rabang et al 2012). This could result in the some of the decreased EFR amplitudes with age observed in this study and elsewhere (Clinard et al 2010;Parthasarathy and Bartlett 2011;Anderson et al 2012). However, modeling the loss of AN fibers and synapses recreated the majority of the trends observed due to age in this study, suggesting peripheral contributions for the decrease in EFR amplitudes at high SNRs and large AM depths.…”
Section: Effects Of Aging In Processing Simultaneous Sam Tonessupporting
confidence: 49%
“…There is a growing body of evidence demonstrating age-related deficits in temporal processing independently of hearing loss (Strouse et al, 1998;Clinard et al, 2010;Hopkins and Moore, 2011;Anderson et al, 2012;Neher et al, 2012;Ruggles et al, 2012;Marmel et al, 2013). Clinard et al (2010) found that age predicted pitch discrimination and magnitude of the FFR at the stimulus frequency, but did not find a significant correlation between the two measures.…”
Section: Discussionmentioning
confidence: 99%
“…Wave amplitudes measured from ABRs also provide insight into the representation of phasic information to short stimuli, based on clearly defined peaks that have been mapped onto specific generators in the auditory brainstem and midbrain (Lev and Sohmer 1972;Rowe 1981;Chen and Chen 1991). Frequency-following responses (FFRs) to tonal carriers or to the modulation envelope (envelopefollowing responses or EFRs), though still not widely used in the clinic, are rapidly gaining prominence as a means of assessing processing of complex sounds from the auditory pathway (Cunningham et al 2001;Aiken and Picton 2008;Swaminathan et al 2008;Basu et al 2010;Clinard et al 2010;Krishnan et al 2010;Parbery-Clark et al 2011;Anderson et al 2012). FFRs and EFRs are evoked in response to longer, often more spectro-temporally complex stimuli (Krishnan 1999(Krishnan , 2002Krishnan et al 2004;Swaminathan et al 2008), and are strongly influenced by rostral brainstem and midbrain generators (Kiren et al 1994;Kuwada et al 2002;Akhoun et al 2010;Chandrasekaran and Kraus 2010;Parthasarathy and Bartlett 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FFRs and EFRs are evoked in response to longer, often more spectro-temporally complex stimuli (Krishnan 1999(Krishnan , 2002Krishnan et al 2004;Swaminathan et al 2008), and are strongly influenced by rostral brainstem and midbrain generators (Kiren et al 1994;Kuwada et al 2002;Akhoun et al 2010;Chandrasekaran and Kraus 2010;Parthasarathy and Bartlett 2012). They have been used to show differences in processing of complex stimuli under various pathological conditions, such as age-related hearing loss, dyslexia, and autism (McAnally and Stein 1997;Chandrasekaran et al 2009;Russo et al 2009;Anderson et al 2012;Clinard and Tremblay 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation